Hello from MrBillDoesMath!
Answer:
l = 2x + 6
Discussion:
From the attachment, where l = length, w = width, and P = perimeter
P = 2l + 2(3x-3)
The Question states that P = 10x + 6 also, so equating the last two items gives
2l + 2(3x-3) = 10x + 6 => 2(3x-3) = 6x - 6
2l + (6x-6) = 10x + 6 =>
2l + 6x - 6 = 10x + 6 => subtract 6x from both sides
2l + (6x - 6x) -6 = (10x - 6x) + 6 => as 6x - 6x = 0 and 10x - 6x = 4x
2l -6 = 4x + 6 => add 6 to both sides
2l = 4x + 6 + 6 => 6 + 6 = 12
2l = 4x + 12 => divide both sides by 2
l = 2x + 6
Thank you,
MrB